Awareness of Mandibular Implant Over Dentures Among Edentulous Patients in Benghazi City: A Cross-sectional Study - Abdelsalam Elhddad; Hawwa Beaayou; Mardeia Hamad; Salma Elnaili (AlQalam Journal of Medical and Applied Sciences, 2025)
Despite the increasing popularity of dental implantology, the utilization of implant-supported or retained over dentures for completely edentulous patients remains below anticipated levels. Therefore, this study aimed to evaluate the awareness of mandibular implants over dentures among completely edentulous patients in Benghazi city. One hundred and fifty questionnaires were distributed among patients undergoing complete denture fabrication, and a closed-end questionnaire. Patients were interviewed in dental clinics with a questionnaire consisting of 10 questions related to socio-demographic data and their knowledge about mandibular implant-supported overdentures. The collected data were statistically analyzed to assess the level of awareness among the participants. It was found that the demographic data represents that 71.5% of the sample were male, while 28.5 % were female. The patients were categorized into four age groups: 40-50 years, 51-60 years, 61-70 years, and over 70 years. About 19.3% of patients denied implant treatment due to cost (37.5%) and 43.2% due to other reasons. However, the majority of participants acquired their awareness of implant-supported dentures from non-medical sources. This study concluded that the current levels of knowledge and awareness regarding lower dental implant-supported overdentures among the patients examined were generally lacking. Almost all patients had no information about implant-supported dental prostheses. Therefore, dentists must educate patients effectively on the importance of these treatments.